STRATEGI PENGELOLAAN KEUANGAN BUMDES MELALUI SIMPAN PINJAM (SEMI KOPERASI) DALAM BENTUK MODAL USAHA BAGI MASYARAKAT DESA BUAHAN - Purnamasari, Ni Wayan Gita; Wirantari, I Dewa Ayu Putri; Yasintha, Putu Nomy (CITIZEN CHARTER, 2023)
BUM Desa Arta Dana has a mission, namely to provide services that maximum in accordance with applicable regulations. Implementation of BUMDES in the Villagestill experiencing problems, namely in program management, employee performance, and community support and participation. This researchusing this type of qualitative research with descriptive methods. Determination technique the informants used were purposive sampling. This researchusing strategic management theory according to Wheelen and Hunger (2003),with four indicators, namely environmental scanning, strategy formulation,strategy implementation, evaluation and control. The results showed that the four indicators were running quite well, it's just that the government and BUMDes environmental scanning indicators have not been able to overcome the shortcomings and threats that occur by optimally utilizing strengths and opportunities, thus affecting the course of other indicators. Keywords: Strategic Management, BUMDES, Savings and Loans